Condition of phase angle for a new VDGA-based multiphase variable phase shift oscillator from 0o to 90o - Kasim K. Abdalla (Institute of Advanced Engineering and Science, 2020)
A novel interesting type of variable phase angle voltage mode oscillator using modern building block has been presented in this paper. The new proposed oscillator configuration which uses four voltage differencing gain amplifier (VDGA) and two grounded capacitors can generate two sinusoidal signals that change out of phase by 0 to 90 degree. It has four floating and explicit voltage mode outputs where every two outputs have the same phase. The circuit is characterized by (i) the condition of phase angle of the oscillation (PO) (this concept is introduced for the first time in this paper) can be tuned electronically (ii) the gain of the floating outputs can be controlled independently (iii) it provides electronic control of condition of oscillation (CO) and independent control of frequency of oscillation (FO). The Total Harmonic Distortion (THD) of the output waveforms was obtained and the results were reasonability values (less than 4.5%). The non-ideal analysis and simulation results are investigated and confirmed the theoretical analysis based upon VDGAs implementable in 0.35μm CMOS technology. Simulation results include time response and frequency response outputs generated by using the PSPICE program.